Small molecules derived carbon dots: synthesis and applications in sensing, catalysis, imaging, and biomedicine - Sharma, Anirudh; Das, Joydeep (Journal of nanobiotechnology, 2019)
Carbon dots (CDs) are the new fellow of carbon family having a size less than 10 nm and attracted much attention of researchers since the last decade because of their unique characteristics, such as inexpensive and facile synthesis methods, easy surface modification, excellent photoluminescence, outstanding water solubility, and low toxicity. Due to these unique characteristics, CDs have been extensively applied in different kind of scientific disciplines. For example in the photocatalytic reactions, drug-gene delivery system, in vitro and in vivo bioimaging, chemical and biological sensing as well as photodynamic and photothermal therapies. Mainly two types of methods are available in the literature to synthesize CDs: the top-down approach, which refers to breaking down a more massive carbon structure into nanoscale particles; the bottom-up approach, which refers to the synthesis of CDs from smaller carbon units (small organic molecules). Many review articles are available in the literature regarding the synthesis and applications of CDs. However, there is no such review article describing the synthesis and complete application of CDs derived from small organic molecules together. In this review, we have summarized the progress of research on CDs regarding its synthesis from small organic molecules (bottom-up approach) via hydrothermal/solvothermal treatment, microwave irradiation, ultrasonic treatment, and thermal decomposition techniques as well as applications in the field of bioimaging, drug/gene delivery system, fluorescence-based sensing, photocatalytic reactions, photo-dynamic therapy (PDT) and photo-thermal (PTT) therapy based on the available literature. Finally, the challenges and future direction of CDs are discussed.